The First Amendment and civil liability - O'Neil, Robert M. (Indiana University Press, 2001)
The First Amendment and Civil LiabilityRobert M. O'NeilA well-known First Amendment advocate explains the new threats to free expression posed by damage suits. This book explores a highly contentious set of issues involving freedom of speech and press. Until very recently, publishers and producers have assumed that, with a few exceptions like libel, freedom of expression was absolute and safe from civil liability in the form of damage awards. In the late 1990s, these complacent assumptions w.